Environment, development, agriculture : integrated policy through human ecology - Glaeser, Bernhard (Abingdon [England] : Routledge, 2010)
This reissue, first published in 1995, focuses on philosophy and social science in human ecology, and includes case studies dealing with the problems of political implementation of development plans and schemes. Part One deals with theory, including a comprehensive introduction to the field and an overview of the conceptual modelling typical in human ecology. Part Two moves towards questions of human behaviour and action, exploring the relationship between environmental ethics and policy in terms of the justification and implementation of human interactions with nature and the environment o.
8 Nature in crisis? A cultural misunderstanding8.1 Technological development, social emancipation and their limitations; 8.2 The dual nature of Homo sapiens; 8.3 Attempts to resolve the contradiction; 8.4 The crisis of nature as a cultural crisis -- prerequisites for controlling instability; 8.5 Conclusion; References; Index.
Includes bibliographical references (pages 157-167) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Environmental ethics; Human ecology; Sustainable agriculture; Sustainable development; Electronic books